Deindustrialization and Tertiarization and the Polarization of Household Incomes: The Example of German Agglomerations - Martin Gornig; Jan Goebel (European Regional Science Association (ERSA), 2014)
Deindustrialization and Tertiarization and the Polarization of Household Incomes: The Example of German Agglomerations The deindustrialization of the economy has left deep scars on cities. It is evident not only in the industrial wastelands and empty factory buildings scattered throughout the urban landscape, but also in the income and social structures of cities. Industrialization, collective wage setting, and the welfare state led to a reduction in income differences over the course of the twentieth century. Conversely, deindustrialization and the shift from primary and secondary to tertiary sectors could result in increasing wage differentiation, especially in agglomerations. Not only is this predicted by economic theory; numerous studies on global cities (Sassen), the dual city (Mollenkopf/Castells), and divided cities (Fainstein et al.) have also identified income polarization as a central phenomenon in the development of major cities. Up to now there has been no systematic statistical analysis of the development of income structures in cities by regional comparison. This is primarily due to the lack of appropriate data for most countries. The present analysis uses a unified German database for comparison of income polarization: the Socio-Economic Panel (SOEP). To enable estimation of the statistical significance of the results, we use different indices of polarization, such as the Reynal-Querol-Index and the Esteban-Ray-Index on the regional level. The tertiarization in Germany since the 1990s has been accompanied by an increasing polarization of household income structures. In agglomerations, this income polarization is even more pronounced than in the more rural regions. Income polarization increased especially rapidly in the period between 2000 and 2006. During this period, not only did the number of households at the extremes of the income distribution increase steadily, but also: "the rich got richer" and "the poor got poorer." The income polarization in Germany is likely to have multiple causes, some of which are directly linked to policies such as the deregulation of the labor market. But extensive deindustrialization has also probably led directly to the weakening of middle income groups, which include many skilled workers. The overall decline in polarization with the renewed growth in manufacturing since 2006 also points in this direction. As a result of this growth, East German conurbations (Berlin, Leipzig, Dresden) have been able to avoid further widening of the income gap. In the West German agglomerations, however, which show a much higher rate of tertiarization, the income polarization has continued increasing.
Keywords: R20; Z13; R11; 330; income polarization; economic change; German agglomerations